Moving From Co-Design to Co-Research: Engaging Youth Participation in Guided Qualitative Inquiry. (9th March 2022) - Clark, Adam T.; Ahmed, Ishrat; Metzger, Stefania; Walker, Erin; Wylie, Ruth
The inclusion of community voices in research is important. Over the years, research training programs have continued to emphasize that engagement with communities at the focus of research can promote thoughtful, sensitive designs (Rivera et al., 2004 ). In this paper, we discuss a method for youth participation in the research process. In an attempt to move beyond "staged and superficial" participation in gathering youth perspectives, we advocate for including co-researchers in the development and modification of fundamental aspects of the research process, from data analysis to the development of additional research questions and collection methods (Guishard & Tuck, 2013 ). In the course of a study designed to enroll middle school students in participatory co-design sessions (Cahill, 2007 ) to aid in the development of educational technologies, it became apparent that our youth participants, as co-researchers, could also aid in the development, analysis, and coding of anonymized interview transcripts; development of themes; and creation of models for behaviors found in the transcripts (Docan-Morgan, 2010 ;Luchtenberg et al., 2020 ). Thus, this paper presents a practical example of a co-research process that includes youth participants, with an emphasis on training in qualitative coding and the fundamentals of research design.